The Texas Society of Pathologists: molded by the legacy of pathology and focused on excellence in medicine for 100 years and beyond - Buja, L. Maximilian (Proc (Bayl Univ Med Cent), 2020)
In 1921, 16 Texas pathologists gathered in Dallas, Texas, to found the Texas Society of Pathologists (TSP). The TSP is now the oldest state pathology society in the USA with continuity traced back to its founding 100 years ago. This article aims to both commemorate the TSP centennial and to provide context for the remarkable success of the society. The article takes a look back and a look forward from 1921. The look back focuses on the development of the field of pathology and the maturation of medicine and pathology in the USA and Texas. The look forward encompasses developments in science, technology, American health care policy, and medicine that have impacted Texas pathologists and influenced proactive initiatives of the TSP. The review of the life and times of the TSP highlights the importance of leaders and leadership in shaping outcomes. Complexities and uncertainties of the contemporary health care scene point to the need for continued strong leadership. The successful past century and hopeful future of the TSP are inextricably linked to the guiding principle of the TSP, which is a focus on continual striving for excellence in medicine.